2015
DOI: 10.1080/10665684.2015.1025616
|View full text |Cite
|
Sign up to set email alerts
|

Should We Use a Capital Framework to Understand Culture? Applying Cultural Capital to Communities of Color

Abstract: Social science research on communities of color has long been shaped by theories of social and cultural capital. This article is a hermeneutic reading of metaphorical capital frameworks, including community cultural wealth and funds of knowledge. Financial capital, the basis of these frameworks, is premised on unequal exchange. Money only becomes capital when it is not spent, but is instead invested, manipulated, and exploited. Metaphorical capitals have been criticized as imprecise, falsely quantitative, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 106 publications
0
12
0
Order By: Relevance
“…Although capital has been described as existing in different forms (e.g., cultural, social, economic, and symbolic), we focus on cultural capital in this study. Cultural capital is observed in embodied, objectified, and institutionalized states (Bourdieu, 1986), and allows individuals to acquire resources, skills, and knowledge through engagement with members of society (Hinton, 2015). Within the literature, disciplinespecific types of cultural capital have been described highlighting advantages that individuals accumulate within specific academic disciplines.…”
Section: Earlier Work Bymentioning
confidence: 99%
“…Although capital has been described as existing in different forms (e.g., cultural, social, economic, and symbolic), we focus on cultural capital in this study. Cultural capital is observed in embodied, objectified, and institutionalized states (Bourdieu, 1986), and allows individuals to acquire resources, skills, and knowledge through engagement with members of society (Hinton, 2015). Within the literature, disciplinespecific types of cultural capital have been described highlighting advantages that individuals accumulate within specific academic disciplines.…”
Section: Earlier Work Bymentioning
confidence: 99%
“…As noted above, students have also been found not to value their own informal methods (Civil 2016), while Oughton (2014) observed that students were more focussed on preparing for qualifications than drawing on their own funds of knowledge. Concerns have also been expressed about the economic metaphor, suggesting that it is more reminiscent of human capital (or 'banking') models of education (Oughton 2010;Hinton 2015).…”
Section: Social Practice Theory and Adult Numeracy Educationmentioning
confidence: 99%
“…Although Hinton (2015) has questioned using a capital metaphor to discuss culture, we believe a FOK framework can talk back to deficit perspectives of non-dominant people. In this sense, FOK raise the ante to demonstrate not all funds relate to financial capital.…”
Section: Funds Of Knowledgementioning
confidence: 94%